Aptamers as potential recognition elements for detection of vitamins and minerals: a systematic and critical review. (17th February 2020) - Heydari, Maryam; Gholoobi, Aida; Ranjbar, Golnaz; Rahbar, Nadereh; Sany, Seyedeh Belin Tavakoly; Mobarhan, Majid Ghayour; Ferns, Gordon A.; Rezayi, Majid
Abstract: Background: Vitamin and mineral deficiencies are prevalent globally, and extensive efforts have been made to assess their status. Most traditional methods are expensive and time-consuming; therefore, developments of rapid, simple, specific, and sensitive methods for the assessment of vitamins and minerals in biological samples are of high importance in research. Aptamers are synthetic nucleic acid single-stranded DNA or RNA that can be synthesized in vitro . They can be engineered to be analyte-specific and have been suggested as a substitute for monoclonal antibodies, due to their high sensitivity and affinity. In addition, aptamers can be chemically synthesized and readily modified for use as biosensors. These features make aptamers a promising tool for the detection of biological analytes. In this review, we provide an overview of the potential use of aptamer-based biosensors. Methods: Search terms were conducted on several online databases, including Google Scholar, PubMed, Scopus, and Science Direct from January 2000 to August 2019. Eligibility criteria were used and quality evaluation was performed. Following the review of 4349 articles, 39 articles met the inclusion criteria. Results: Aptasensors have recently been developed for the detection of vitamins by using optical methods, with a detection range from 74 pM to 204 pM, and lower limit of detection of 2.4 pM. Both electrochemical and optical methods have been used for detection of minerals, however electrochemical methods show a wider linear range and lower detection limits compared to optical methods with a wide linear range from 0.2 fM to 1.0 mM and limit of detection of 14.7 fM. Conclusion: The current report reviews recent developments in aptamer-based biosensors for detection of vitamins and minerals. Studies have shown that aptasensors' properties are suitable for the quantification of vitamins and minerals with high sensitivity, affinity, and specificity. Nevertheless, the limitations and future directions of aptamers require further research and new technological innovation.